Website Development for the Openness of Educational Information in Bandung, Indonesia - Hernawati, Elis; Dwi Mayangsari, Ira (IJAIT (International Journal of Applied Information Technology), 2017)
The problems of education in Kota Bandung have not resolved satisfactorily. Some examples of chronic educational problems are the lack of openness of information about the use of government grants by schools, the quota for needy students, and school levies. The cause of this problem is the absence of the media in the form of websites that can be accessed by parents openly to get information about student academic progress and the problems of education in the city. In this study, will create a web application in the form of online mediain accordance with the character of the people of Bandung. The Web producing news and information based on users' preferences, and providing spaces for open public discussion. This study uses an Evolutionary Prototyping method. This approach is suitable to be used so that the process of application development is done gradually and faster because there is interaction with the user during the process. This website can encompass all residents to access the openness of educational information in Kota Bandung. TheWeb testing is done by the user, the test results show three functional items on the web are login member, search news and manage the article. The test result shows each item received by the user. After testing, the website is hosted by the domain name intipbdg.org (Informasi dan Tips Pendidikan Bandung).